Implementasi Asesmen Formatif Berbasis Web pada Pembelajaran Fikih di MAN 1 Boyolali - Dwi Sulistyowati; Purnomo (Information Technology Education Department, 2025)
This study aims to analyze the implementation and impact of web-based formative assessment in Fiqh learning at MAN 1 Boyolali. The research employs a qualitative approach using a case study design. Data were collected through observations, interviews, and documentation involving Fiqh teachers, the school principal, and nine students from grades X, XI, and XII. The findings indicate that teachers design web-based formative assessments by aligning them with learning outcomes, students’ characteristics, and the digital context of the school. The assessments are conducted continuously through a web system that facilitates evaluation, reflection, and real-time feedback. The implementation of web-based assessments has been shown to enhance students’ motivation, engagement, and conceptual understanding of Fiqh, while simultaneously fostering values of honesty and responsibility.